Aldosterone to Renin Ratio as a Screening Instrument for Primary Aldosteronism in a Middle-Aged Population with Atrial Fibrillation - Mourtzinis, Georgios; Ebrahimi, Ahmad; Gustafsson, Helena; Johannsson, Gudmundur; Manhem, Karin (Hormone and Metabolic Research, 2017)
Atrial fibrillation seems to be overrepresented among patients with primary aldosteronism. The aim of this study was to determine the usefulness of aldosterone to renin ratio as a screening instrument for primary aldosteronism in an atrial fibrillation population with relatively low cardiovascular risk profile. A total of 149 patients <65 years and with history of AF were screened for primary aldosteronism using aldosterone to renin ratio. Pathologically increased aldosterone to renin ratio (>65 pmol/mIU) was found in 15 participants (10.1%). Further investigation of the positive screened participants and confirmatory saline infusion test resulted in a diagnosis of primary aldosteronism in four individuals out of 149 (2.6%). Three out of the four individuals with primary aldosteronism had previously been diagnosed with hypertension, but only one out of the four had uncontrolled blood pressure, that is, >140/90 mmHg. All participants had normal potassium levels. Individuals with increased aldosterone to renin ratio had significantly higher mean systolic and diastolic blood pressure in comparison to participants with normal aldosterone to renin ratio (136 vs. 126 mmHg, p=0.02 and 84 vs. 78 mmHg, p=0.02). These findings suggest that assessment of aldosterone to renin ratio can be useful for identification of underlying primary aldosteronism in patients with diagnosed atrial fibrillation and hypertension in spite of well controlled blood pressure and normokalemia.
Keywords: atrial fibrillation; hypertension; aldosteronism; aldosterone to renin ratio